Sally Sloane, Ron Manton, Edwin Godwin, Arthur Burchan and Fred Holland perform traditional songs in the John Meredith folklore collection. - Sloane, Sally, 1894-1982; Manton, Ron; Godwin, Edwin; Burchan, Arthur; Holland, Fred; Meredith, John, 1920-2001 (1960)
Folkloric recording.
Wild colonial boy / Sally Sloane -- Humping old blue / Rod Manton -- Wild colonial boy (three versions) / Rod Manton -- Bold Jack Donohue / Edwin Godwin --Jollylee / Edwin Godwin -- The maid and the magpie / Edwin Godwin -- Les Darcy / Arthur Burchan -- Wild colonial boy / Arthur Burchan -- Waltzing Matilda / Arthur Burchan --Good luck to the Barley Mow / Arthur Burchan -- White man let me go / Fred Holland.
Recorded during 1960.
Digital master available
Summary not yet available.
Keywords: Folk songs, English -- Australia; Folk music -- Australia